(untitled) (International scientific-electronic journal “Pioneering studies and theories”, 2026)
This article analyzes the current state and specific features of green innovation development in Uzbekistan’s industrial enterprises. The study emphasizes the role of green technologies in improving resource efficiency, reducing greenhouse gas emissions, and ensuring sustainable industrial growth. The research is based on analytical, comparative, and statistical methods, as well as an examination of national development strategies and regulatory documents. The findings reveal that despite the adoption of strategic policies supporting green transformation, industrial enterprises face significant barriers such as outdated technological infrastructure, insufficient financial resources, and limited human capital. At the same time, strengthening state support mechanisms and promoting circular economy principles are identified as key drivers for accelerating green innovation adoption in Uzbekistan’s industrial sector.